Intra-party Democracy: The Practices on the Election of Prosperous Justice Party President - Jamaludin Ghafur; Saifudin Saifudin (Sriwijaya Law Review, 2020)
This paper will analyze the arrangements and practices for the election of chairperson (president) of the Prosperous Justice Party as one of the party's instruments in implementing intra-party democracy. There are two main issues to be discussed, namely: (i) has the regulation of the election of the president of the Prosperous Justice Party reflected democratic arrangements? (ii) has the democratic election been conducted in the Presidential Election for the Prosperous Justice Party? To answer this question, researchers examine all the laws and regulations relating to the legal issue in question. The laws and regulations referred to fall into two categories, namely primary and secondary legal materials. The results showed that both in terms of formulation of rules and practice, the election of the president of the Prosperous Justice Party is still far from democratic values. It is caused by the following five factors: (1) the right of nomination is not open to all party members but is nominated by the chairman of the Advisory Council, (2) the right to vote does not involve broad party elements but only becomes the authority of the members of the Advisory Council, (3) presidential candidates parties are not elected through a voting mechanism, but by appointment (acclamation), (4) the nature of the election is not competitive because it is always only followed by a single candidate, and (5) there is a limitation of the term of office of five years, but there is no limit on how many times. It has the potential for a party presidential position to be held by one person for an unlimited period.